Formulation, optimization and characterization of cationic polymeric nanoparticles of mast cell stabilizing agent using the Box–Behnken experimental design - Gajra B.; Patel R.R.; Dalwadi C. (My University, 2025)
Objective: The present research work was intended to develop and optimize sustained release of biodegradable chitosan nanoparticles (CSNPs) as delivery vehicle for sodium cromoglicate (SCG) using the circumscribed Box–Behnken experimental design (BBD) and evaluate its potential for oral permeability enhancement. Methods: The 3-factor, 3-level BBD was employed to investigate the combined influence of formulation variables on particle size and entrapment efficiency (%EE) of SCG-CSNPs prepared by ionic gelation method. The generated polynomial equation was validated and desirability function was utilized for optimization. Optimized SCG-CSNPs were evaluated for physicochemical, morphological, in-vitro characterizations and permeability enhancement potential by exvivo and uptake study using CLSM. Results: SCG-CSNPs exhibited particle size of 200.4 ± 4.06nm and %EE of 62.68 ± 2.4% with unimodal size distribution having cationic, spherical, smooth surface. Physicochemical and invitro characterization revealed existence of SCG in amorphous form inside CSNPs without interaction and showed sustained release profile. Ex-vivo and uptake study showed the permeability enhancement potential of CSNPs. Conclusions: The developed SCG-CSNPs can be considered as promising delivery strategy with respect to improved permeability and sustained drug release, proving importance of CSNPs as potential oral delivery system for treatment of allergic rhinitis. Hence, further studies should be performed for establishing the pharmacokinetic potential of the CSNPs. © 2015 Taylor & Francis.